Climate Change Effects on North American Fish and Fisheries to Inform Adaptation Strategies. Issue 9 (24th September 2021) - Paukert, Craig; Olden, Julian D.; Lynch, Abigail J.; Breshears, David D.; Christopher Chambers, R.; Chu, Cindy; Daly, Margaret; Dibble, Kimberly L.; Falke, Jeff; Issak, Dan; Jacobson, Peter; Jensen, Olaf P.; et al.
Abstract : Climate change is a global persistent threat to fish and fish habitats throughout North America. Climate‐induced modification of environmental regimes, including changes in streamflow, water temperature, salinity, storm surges, and habitat connectivity can change fish physiology, disrupt spawning cues, cause fish extinctions and invasions, and alter fish community structure. Reducing greenhouse emissions remains the primary mechanism to slow the pace of climate change, but local and regional management agencies and stakeholders have developed an arsenal of adaptation strategies to help partially mitigate the effects of climate change on fish. We summarize common stressors posed by climate change in North America, including (1) increased water temperature, (2) changes in precipitation, (3) sea level rise, and (4) ocean acidification, and present potential adaptation strategies that fishery professionals may apply to help vulnerable fish and fisheries cope with a changing climate. Although our adaptation strategies are primarily from North America, they have broader geographic applicability to fish and aquatic biota in other jurisdictions. These strategies provide opportunities for managers to mitigate the effects of climate change on fish and fish habitat while needed global policies to reduce greenhouse gas emissions emerge, which may offer more lasting solutions.